Immediate Effects of Body Checking Behaviour on Negative and Positive Emotions in Women with Eating Disorders: An Ecological Momentary Assessment Approach. (20th June 2015) - Kraus, Nicole; Lindenberg, Julia; Zeeck, Almut; Kosfelder, Joachim; Vocks, Silja
Abstract Objectives Cognitive‐behavioural models of eating disorders state that body checking arises in response to negative emotions in order to reduce the aversive emotional state and is therefore negatively reinforced. This study empirically tests this assumption. Methods For a seven‐day period, women with eating disorders (n = 26) and healthy controls (n = 29) were provided with a handheld computer for assessing occurring body checking strategies as well as negative and positive emotions. Serving as control condition, randomized computer‐emitted acoustic signals prompted reports on body checking and emotions. Results There was no difference in the intensity of negative emotions before body checking and in control situations across groups. However, from pre‐ to post‐body checking, an increase in negative emotions was found. This effect was more pronounced in women with eating disorders compared with healthy controls. Discussion Results are contradictory to the assumptions of the cognitive‐behavioural model, as body checking does not seem to reduce negative emotions. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.